Konsep Penataan Lanjutan Jalur Pejalan Kaki Di Kota Surabaya - Pramita, Elen Lidya; Wardhani, Dian Kusuma; Sari, Kartika Eka (Fakultas Teknik, Universitas Brawijaya, 2013)
Based on Spatial Planning of Surabaya in 2010-2030, the government was efforted to manage the road network infrastructure for pedestrians, which will be redesigned 12 pedestrian ways that were existed since 2010 to 2012. However, the condition of pedestrian facilities were still underutilized by citizen that was seen from the lack of pedestrian activity carried on pedestrian ways redesigned . The main purpose of the research was known the design concept in redesigned pedestrian way in Surabaya. This research was used Multi Criteria Evaluation (MCE) as a dsecriptive method and site analysis as an evaluative method. The result of Multi Criteria Evaluation (MCE) was the location of pedestrian ways that researched such as Jalan Raya Dharmo, Jalan Raya Gubeng dan Kawasan Wijaya Kusuma. The result of site analysis such as movement and activity was caused by needs, land use and attractive activity; low utilized caused by no attractive activity and motivation to walk around; motorcycles are easy to access the pedestrian way; the existence of trades liven up the atmosphere. The design concept in pedestrian way redesigned Surabaya City were safety and confortable with sufficient dimension and facilities, have an attractive atmosphere with activity support, and easily accessible to all age ranges and disabilities users.Keywords: design concept, pedestrian way, Surabaya City, site analysis.